Life Goals and Coping of Elderly Women Living in Poverty - Mangaoil, Armina; Ramos, Rizandrea Judela; Rungduin, Teresita; Baclagan, Tito; Rantael, Maria Luz (Journal of Interdisciplinary Perspectives, 2024)
This qualitative research study explored the circumstances of elderly women living in poverty during the COVID-19 pandemic and examined the various life goals they developed over their life course. Nine women, aged 65 to 85, residing in Metro Manila and classified as beneficiaries of the government’s Pantawid Pamilyang Pilipino Program (a conditional cash transfer program implemented by the Department of Social Welfare and Development), participated in phone interviews. These interviews explored their different life goals, ways of achieving them, and the impact of the pandemic. The results suggest that while goals aimed at improving their financial situation are prominent among elderly women in poverty, most of their goals are directed toward the betterment of people significant to them. A key factor they consider helpful in achieving their goals is social or external support. However, challenges brought by the pandemic have significantly shifted their focus to simpler goals, such as regaining the freedom to engage in outdoor activities and ensuring survival.